Performance Assessment of Existing Farmers’ Association for Water Users - Fauzi, Meftahol; Juwono, Pitojo Tri; Bisri, M.; Suhartanto, Ery (Journal of Ecohumanism, 2025)
This research intends to assess the existing performance of farmers’ association for water users (P3A). Commonly, the activity of irrigation management is started from the stages of design, construction until operation and maintenance, it is needed the collaboration and participation of P3A that is spreading in the Malang Regency. The methodology consists of literature collecting and data analysis. Data that are used in this research is secondary data that influence the performance of farmers institution performance (P3A) in Malang Regency. The assessment of performance uses the questionaries form that is answered based on the response from farmers group which are as the respondents for every question that will be given the scores regarding to the question. The result shows that 30% of P3A institutions is developing category, however, 70% is developed category.